Multiple skills and medium enterprises’ performance in Punjab Pakistan: a pilot study - Ahmad, Israr; Ahmad, Shuhymee (Academic Research Publishing Group, 2018)
This research study aims to assess the face validity and reliability of the construct of skills set and explore quantitatively a small sample of data on the determinants of performance of MEs in Punjab, Pakistan. The survey method approach was adopted to collect the data from MEs’ owners or managers through 41 usable questionnaires and adopted the stratified random sampling method. Therefore, the validity and reliability of the instruments were examined through a panel of experts from industry and academia and also a small sample of the data analyzed by using SPSS version 23.0 for Mac. While, results confirmed the reliability and face validity of the adapted instruments in the pilot study.